PERAN EKONOMI DIGITAL DALAM MENDORONG PERTUMBUHAN EKONOMI NASIONAL - Krismonica Lubis; Bakhtiar Efendi (ITB AAS Indonesia Surakarta, 2023)
Indonesia's digital economy has very promising prospects if managed well because its growth exceeds Indonesia's economic growth. Indonesia is experiencing an overall increase in the digital economy in finance, health, tourism, industry, education, and so on. This has an effect on increasing the national economy. This research is descriptive qualitative research with a literature study research method through literature study. The results of the study state that the potential of the digital economy greatly affects national economic growth, making Indonesia the largest market share of the digital economy. The existence of the digital economy is strongly felt by the community, thus forcing related parties to design new strategies by adopting digitalization, which is dominated by innovations in technology, information, communication, and the increasing development of internet networks. To achieve the success of the digital economy, the support of a workforce / human resources with special skills in technology is also one of the important basic pillars, the innovation ecosystem is also important to revive the digital economy, as well as public services, digital economy, and good governance and digital strategy.